The Role of Oxidative Stress in Dupuytren’s Disease Pathogenesis - Nicula, Valeriu; Decea, Nicoleta; Ciuce, Constantin (Medicine and Pharmacy Reports, 2014)
Background. Dupuytren’s Disease (DD) means the fibrous retraction of palmar and digital aponeurosis. Up to now, the intrinsic ethiopathogenetic mechanisms of DD are still not completely known. Aims. We aimed to investigate:1) the relationship between oxidative stress, inflammatory mechanisms and DD; 2) the alterations induced by diabetes mellitus (DM) in the aforementioned pathogenetic mechanisms a of DD. Material and method. 36 cases bearing DD lesions, as well as 25 control cases were selected between 2005-2007. According to presence of DM, test group was further divided into two sub-groups (presence of DM, n=28; absence of DM, n=8). Collection of urine and saliva was performed for all included cases. Malondialdehyde (MDA), hydrogen donor activity (HD) were assessed on both urinary and salivary samples. Also, ceruloplasmin (CP) was measured in saliva for all patients. Results. MDA levels were superior in test group as compared to control group for urinary samples (p=0.011). HD, CP presented lower values in DD group. Patients presenting DD and DM association recorded significantly different levels of urinary MDA (p=0.004), HD (p=0.045) as well as salivary CP levels (p=0.025) as compared to DD with no glycemic equilibrium alterations group. Conclusions. Dupuytren contracture, both in the form of stand-alone disease and secondary manifestation of DM is associated with oxidative balance alteration and oxidative injury in saliva and urine. By means of innate mechanisms, diabetes alleviates the DD-specific oxidative injury.